2006
DOI: 10.1212/01.wnl.0000218215.43328.88
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an oculomotor biomarker of preclinical Huntington disease

Abstract: The authors examined oculomotor function to identify a biomarker of disease progression in genetically confirmed preclinical and early clinical Huntington disease (HD). Initiation deficits of voluntary-guided, but not reflexive, saccades were characteristic of preclinical HD. Saccadic slowing and delayed reflexive saccades were demonstrated in clinical but not preclinical HD. Saccadic measures provide biomarkers of disease progression in both preclinical and early clinical stages of HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 9 publications
8
68
1
1
Order By: Relevance
“…Initiation deficits of voluntary guided saccades, saccadic slowing, and delayed reflexive saccades were present. [84][85][86] When compared with controls, premanifest individuals also show impairment in the antisaccadic and memoryguided tasks and longer latencies, especially during the latter. Furthermore, the saccadometry research tool has proved valuable in separating premanifest, manifest, and controls who showed an increased incidence of early saccades with unusually short latencies.…”
Section: Clinical Ocular Motor Findingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Initiation deficits of voluntary guided saccades, saccadic slowing, and delayed reflexive saccades were present. [84][85][86] When compared with controls, premanifest individuals also show impairment in the antisaccadic and memoryguided tasks and longer latencies, especially during the latter. Furthermore, the saccadometry research tool has proved valuable in separating premanifest, manifest, and controls who showed an increased incidence of early saccades with unusually short latencies.…”
Section: Clinical Ocular Motor Findingsmentioning
confidence: 97%
“…Furthermore, the saccadometry research tool has proved valuable in separating premanifest, manifest, and controls who showed an increased incidence of early saccades with unusually short latencies. [84][85][86][87][88][89] Manifest patients early in the course of their disease, exhibit reduced saccadic velocity, 78,81,90 impaired initiation of saccades, an increase in the frequency of square-wave jerks, and an increase in saccadic latencies, that is greater for voluntary than reflexive saccades. They have excessive distractibility during attempted fixation, even when specifically instructed to maintain fixation on a centrally located target.…”
Section: Clinical Ocular Motor Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] In addition, subtle oculomotor and other movement peculiarities and neuropsychiatric changes have been reported in some mutation-positive individuals prior to the onset of clinical signs and symptoms sufficient for diagnosis. [8][9][10][11][12] However, the search for presymptomatic changes in cognition among those with the huntingtin mutation has met with mixed results. Several investigations reported no significant differences in neuropsychological functioning between those with and those without the Huntington's disease mutation.…”
Section: Introductionmentioning
confidence: 99%
“…1 A commonly used measure of cognitive inhibition is the antisaccade (AS) task, which requires suppression of a visually guided saccade toward a target and generation of voluntary saccade in the opposite direction. 2,3 The percentage of correct AS responses is sensitive to frontal lobe dysfunction in aging, 4 schizophrenia, [5][6][7][8] Huntington disease (HD), 9,10 and a variety of neurodegenerative dementias. [11][12][13] Despite the potential clinical utility of the AS task in evaluating neurologic function, current methods of evaluation are limited to informal bedside evaluation or the use of expensive eye-tracking equipment.…”
mentioning
confidence: 99%